The growing world of small heat shock proteins: from structure to functions - Carra, Serena; Bukau, Bernd (Cell stress & chaperones, 2017)
Small heat shock proteins (sHSPs) are present in all kingdoms of life and play fundamental roles in cell biology. sHSPs are key components of the cellular protein quality control system, acting as the first line of defense against conditions that affect protein homeostasis and proteome stability, from bacteria to plants to humans. sHSPs have the ability to bind to a large subset of substrates and to maintain them in a state competent for refolding or clearance with the assistance of the HSP70 machinery. sHSPs participate in a number of biological processes, from the cell cycle, to cell differentiation, from adaptation to stressful conditions, to apoptosis, and, even, to the transformation of a cell into a malignant state. As a consequence, sHSP malfunction has been implicated in abnormal placental development and preterm deliveries, in the prognosis of several types of cancer, and in the development of neurological diseases. Moreover, mutations in the genes encoding several mammalian sHSPs result in neurological, muscular, or cardiac age-related diseases in humans. Loss of protein homeostasis due to protein aggregation is typical of many age-related neurodegenerative and neuromuscular diseases. In light of the role of sHSPs in the clearance of un/misfolded aggregation-prone substrates, pharmacological modulation of sHSP expression or function and rescue of defective sHSPs represent possible routes to alleviate or cure protein conformation diseases. Here, we report the latest news and views on sHSPs discussed by many of the world’s experts in the sHSP field during a dedicated workshop organized in Italy (Bertinoro, CEUB, October 12-15, 2016).
Gesehen am 26.04.2018